The radical orthodoxy reader - Milbank, John; Oliver, Simon (Radical orthodoxy, 2009)
What is radical orthodoxy? -- Radical orthodoxy : from participation to later modernity / Simon Oliver -- Radical orthodoxy : a conversation / Rupert Shortt -- Postmodern critical augustinianism : a short summa in forty-two responses to unasked questions / John Milbank -- Theology and philosophy, faith and reason -- Truth and vision / John Milbank -- Duns Scotus : his historical and contemporary significance / Catherine Pickstock -- Theology and the secular -- Spatialization : the middle of modernity / Catherine Pickstock -- Political theology and the new science of politics / John Milbank -- Christ and gift -- Christ the exception / John Milbank -- The schizoid Christ / Graham Ward -- Church and Eucharist -- Thomas Aquinas and the quest for the Eucharist / Catherine Pickstock -- The ontological scandal / Graham Ward -- Politics and theology -- A fire strong enough to consume the house : the wars of religion and the rise of the nation state / William Cavanaugh -- Materialism and transcendence / John Milbank -- Afterward: The grandeur of reason and the perversity of rationalism : radical orthodoxy's first decade / John Milbank